Saturated fatty acids differently affect mitochondrial function and the intestinal epithelial barrier depending on their chain length in the in vitro model of IPEC-J2 enterocytes - Guerbette, Thomas; Rioux, Vincent; Bostoën, Mégane; Ciesielski, Vincent; Coppens-Exandier, Hugo; Buraud, Marine; Lan, Annaïg; Boudry, Gaëlle (Frontiers in Cell and Developmental Biology, 2024)
Maintenance of the intestinal barrier mainly relies on the mitochondrial function of intestinal epithelial cells that provide ATP through oxidative phosphorylation (OXPHOS). Dietary fatty acid overload might induce mitochondrial dysfunction of enterocytes and may increase intestinal permeability as indicated by previous in vitro studies with palmitic acid (C16:0). Yet the impact of other dietary saturated fatty acids remains poorly described. To address this question, the in vitro model of porcine enterocytes IPEC-J2 was treated for 3 days with 250 µM of lauric (C12:0), myristic (C14:0), palmitic (C16:0) or stearic (C18:0) acids. Measurement of the transepithelial electrical resistance, reflecting tight junction integrity, revealed that only C16:0 and C18:0 increased epithelial permeability, without modifying the expression of genes encoding tight junction proteins. Bioenergetic measurements indicated that C16:0 and C18:0 were barely β-oxidized by IPEC-J2. However, they rather induced significant OXPHOS uncoupling and reduced ATP production compared to C12:0 and C14:0. These bioenergetic alterations were associated with elevated mitochondrial reactive oxygen species production and mitochondrial fission. Although C12:0 and C14:0 treatment induced significant lipid storage and enhanced fusion of the mitochondrial network, it only mildly decreased ATP production without altering epithelial barrier. These results point out that the longer chain fatty acids C16:0 and C18:0 increased intestinal permeability, contrary to C12:0 and C14:0. In addition, C16:0 and C18:0 induced an important energy deprivation, notably via increased proton leaks, mitochondrial remodeling, and elevated ROS production in enterocytes compared to C12:0 and C14:0.